EDUKASI PENERAPAN 5M DI MASA PANDEMI COVID-19 MELALUI METODE AUDIOVISUAL - Saroinsong, Shelly; Rakinaung, Natalia; Geneo, Martinus (Lasalle Health Journal, 2024)
Introduction: The COVID-19 outbreak has made health problems around the world very serious. This virus really affects everyone's lives, from health, work, relationships with other people, trust, to school. Objective: This research aims to analyze the effectiveness of providing health education about the 5Ms during the Covid-19 pandemic using audiovisual methods for junior high school students. Negeri 8 Manado. Method: this research is quantitative research using a Quasi Experimental research method with a one group research design, namely pre-test and post-test. The target population for this research was school age students at SMP N 8 Manado, total 217 students. The sampling process in this research used purposive sampling with a total sample of 142 people. For bivariate analysis use the Wilcoxon test. Results: Wilcoxon test results show that there is a significant difference in the level of knowledge and readiness of respondents before and after being given health education (p-value < α 0.05). Conclusion: So, through the results of the analysis, it can be concluded that providing health education regarding the implementation of 5M during the Covid-19 pandemic has an effective impact on improving the knowledge and attitudes of school-age children.